Postcolonial Peru’s fiscal bases, 1821-1845 - Rojas Rojas, Rolando (2019)
This paper study and discuss state financing sources and changes introduced in the Peruvian fiscal structure. To do so, we work in a documented way about indirect and ethnic taxes in the regime of liberal direct taxes. We reconstruct the dynamics of a time of transition in taxation because the State financial income was a combination of old and new taxes: indigenous tax, maritime customs, mining taxes, and «industrial patent». Finally, it asserts tax collection is oriented -almost completely- to the payment of civil and military bureaucracy; that is, for the State’s own upkeep.